Travels of Bollywood cinema from Bombay to LA - Roy, Anjali Gera.; Chua, Beng Huat. (New Delhi ; Oxford : Oxford University Press, 2012)
Bringing together perspectives on Indian cinema from different disciplinary and geographical locations, this volume shows that Bollywood cinema has always crossed borders and boundaries.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Motion pictures, Indic -- History